2005
DOI: 10.1177/0884217505281857
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Responses of a Preterm Infant to Kangaroo Care

Abstract: A 35-week old preterm infant's behavior was fussy and restless in the open crib, but he calmed and fell asleep immediately on being placed skin-to-skin on his mother's chest. Heart rate variability (HRV), a noninvasive method to assess the autonomic nervous system's influence on heart rate, was increased with fussy behavior in the open crib and decreased with sleep during kangaroo care (KC). KC produced changes in behavior and HRV that are illustrative of decreasing stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
3
35
0
2
Order By: Relevance
“…In addition to maternal nurturing care, babies' developmental progress in this study is attributed to a warm comfortable KMC environment resulting in the baby's ability to sleep quietly for longer periods of time and rapid weight gain. Weight gain is partly associated to the baby's ability to sleep longer, thus conserving energy and preserving caloric expenditure toward growth [17,21]. With KMC, babies have been observed to spend longer hours sleeping, with other studies linking KMC to a baby's natural habitat [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to maternal nurturing care, babies' developmental progress in this study is attributed to a warm comfortable KMC environment resulting in the baby's ability to sleep quietly for longer periods of time and rapid weight gain. Weight gain is partly associated to the baby's ability to sleep longer, thus conserving energy and preserving caloric expenditure toward growth [17,21]. With KMC, babies have been observed to spend longer hours sleeping, with other studies linking KMC to a baby's natural habitat [22].…”
Section: Discussionmentioning
confidence: 99%
“…KC is defined as skin-to-skin contact between a mother and her newborn and may begin soon after birth or be delayed for several weeks (CondeAgudelo, Diaz-Rossello, & Belizan, 2003;DiMenna, 2006). Proponents of KC believe that it promotes weight gain, decreases hospital stay, increases skin temperature, maintains higher oxygen saturation, increases physiological stability including heart and respiratory rate, increases sleep time and decreases irritability of preterm and low birth weight neonates (McCain, Ludington-Hoe, Swinth, & Hadeed, 2005;Rojas et al, 2003). However, a recent Cochrane Review of KC for low birth weight infants concluded that while KC improved mother-infant bonding and reduced severe illness, infection, breast-feeding problems and maternal dissatisfaction with method of care there was still not enough evidence to suggest that KC is an effective alternative to standard care (Conde-Agudelo et al, 2003).…”
Section: Touch and Developmentmentioning
confidence: 99%
“…[30] KC also stabilizes vagally-controlled autonomic processes in newborns. [31] KC is known to improve many of the adverse symptoms characterizing NAS, i.e. irritability, poor sleep, poor state regulation, and stress.…”
Section: Discussionmentioning
confidence: 99%